Complementary medicine in orthopaedic and trauma surgery: a cross-sectional survey on usage and needs - Anica Kilper; Alexander Müller; Roman Huber; Niklas Reimers; Ludwig Schütz; Ann-Kathrin Lederer (BMJ Open)
Objectives Complementary and alternative medicine (CAM) is frequently used in Western countries within general medicine and internal medicine. Information on the use in orthopaedic and trauma surgery is widely lacking. The aim of this study was to investigate usage and needs regarding CAM for these patients.Design Prospective paper-based, pseudoanonymous, cross-sectional survey.Setting From August to December 2018, a questionnaire composed of 17 questions was distributed to all eligible patients.Participants In-house patients in orthopaedic and trauma surgery at a high-volume medical centre in Germany.Primary and secondary outcome measures Previous or current usage of CAM, interest and requests towards CAM as well as communication about CAM.Results Overall, 457 orthopaedic and trauma surgical patients took part in the survey. They were on average 52 years old and 54% were male. Most of the patients were admitted due to bone fractures and most underwent operative therapy. Previous or current CAM usage was stated by 76% and 30% of patients, respectively. Most of the patients stated to be interested in usage of CAM and demanded for more clinical usage of CAM and reliable information about CAM. More than 90% of patients did not discuss CAM interest or usage with their treating physicians. Patients stated that physicians should have knowledge about CAM. They wish to be treated in a holistic manner and want to strengthen self-efficacy.Conclusions Usage of CAM of patients in orthopaedic and trauma surgery appears to be high. Only a few patients discuss their interest and usage of CAM with their treating physician. Therefore, surgeons should ask their patients about CAM and should consider evidence-based CAM approaches for complementary treatment.Trial registration number DRKS0001544.